2020
DOI: 10.1063/1.5142275
|View full text |Cite
|
Sign up to set email alerts
|

Equations of State for the Thermodynamic Properties of Binary Mixtures for Helium-4, Neon, and Argon

Abstract: Based upon the conceptual design reports for the Future Circular Collider cryogenic system, the need for more accurate thermodynamic property models of cryogenic mixtures of noble gases was identified. Both academic institutes and industries have identified the lack of a reliable equation of state for mixtures used at very low temperatures. Detailed cryogenic architecture modeling and design cannot be carried out without accurate fluid properties. Therefore, the helium-neon equation was the first goal of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Multi-parameter mixture Helmholtz energy models are the most accurate option for such calculations and should be used where available. Tkaczuk et al 156 have reported accurate Helmholtz energy EOS models with binaryspecific functions for helium and neon, helium and argon and neon and argon mixtures. For refrigerant mixtures that include hydrogen with the noble gases, an extension of the work by Beckmu ¨ller et al is underway; however, this approach will be limited by the use of normal rather than equilibrium hydrogen within the GERG-2008 framework.…”
Section: Thermodynamic Property Descriptions For Hydrogen Liquefactionmentioning
confidence: 99%
“…Multi-parameter mixture Helmholtz energy models are the most accurate option for such calculations and should be used where available. Tkaczuk et al 156 have reported accurate Helmholtz energy EOS models with binaryspecific functions for helium and neon, helium and argon and neon and argon mixtures. For refrigerant mixtures that include hydrogen with the noble gases, an extension of the work by Beckmu ¨ller et al is underway; however, this approach will be limited by the use of normal rather than equilibrium hydrogen within the GERG-2008 framework.…”
Section: Thermodynamic Property Descriptions For Hydrogen Liquefactionmentioning
confidence: 99%
“…For that reason, the orthogonal distance between a point and the phase envelope has been used as an error metric in other works. 121 Here, we consider only pressure deviations, emphasizing that near-critical model predictions will be unfairly penalized by this error metric. We further emphasize that deviations are relative to the nearest nominal isotherm.…”
Section: Modelsmentioning
confidence: 99%
“…At low pressure, deviations in pressure are meaningful, and in parts of the critical region, deviations in composition are more meaningful because the slope of the isotherm (in the coordinates of the plot) goes to infinity. For that reason, the orthogonal distance between a point and the phase envelope has been used as an error metric in other works . Here, we consider only pressure deviations, emphasizing that near-critical model predictions will be unfairly penalized by this error metric.…”
Section: Modelsmentioning
confidence: 99%
“…This issue still represents a significant challenge either for measurements or theoretical derivation [100]. As a way of example, binary mixtures have been only recently tested [101].…”
Section: Characterization Of Liquid-vapor Systemsmentioning
confidence: 99%